2013
DOI: 10.1111/jphp.12130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for effect of hypothermia on the disposition of 4-nitrophenol in rats by in-vitro metabolism study and rat liver perfusion system

Abstract: Graduate School of Biomedical Sciences, Nagasaki University, 1-14 Bunkyo-machi, 10Nagasaki 852-8521, Japan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Moreover, the concentration of midazolam at 0 min estimated by analyses of a two-compartment model was increased slightly under hypothermia ( Figure 2) and the distribution volume of the central compartment (V c ) was significantly lower at 28°C than at 37°C (data not shown). In our previous study, the initial concentrations of several drugs (phenolsulfonphthalein, indocyanine green, fluorescein isothiocyanate-dextran, 4-nitrophenol) after intravenous injection were also increased according to body temperature [31,32]. Tveita et al reported that the blood volume and the plasma volume were decreased post-hypothermia [33].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the concentration of midazolam at 0 min estimated by analyses of a two-compartment model was increased slightly under hypothermia ( Figure 2) and the distribution volume of the central compartment (V c ) was significantly lower at 28°C than at 37°C (data not shown). In our previous study, the initial concentrations of several drugs (phenolsulfonphthalein, indocyanine green, fluorescein isothiocyanate-dextran, 4-nitrophenol) after intravenous injection were also increased according to body temperature [31,32]. Tveita et al reported that the blood volume and the plasma volume were decreased post-hypothermia [33].…”
Section: Discussionmentioning
confidence: 87%